The employment relation and spatial division of labor: a hypothesis - Clark, G (Routledge, 1981)
The relationship between labor and capital is one of mutual antagonism and interdependence. Conflict occurs between labor and capital over control of the production process and conditions of employment. However, both classes need one another in order to produce and sustain a livelihood. Spatial decentralization of production and the division of labor can be interpreted as an explicit bargaining strategy of the firm designed to control the power of labor and reinforce the authority of capital. Firms prefer to externalize their labor markets although local conditions, skill requirements, and union power may force internalization and consequently higher costs. Small and relatively depressed local labor markets are favored locations for firms producing standardized commodities. Firms that require specific skills and technical expertise are, on the other hand, more dependent upon the locational preferences of labor. Spatial concentration and agglomeration of production involving both skilled and unskilled workers may not be in the best interests of a firm because of their different labor market strategies related to their preferred employment relations.